Lipomatous Soft Tissue Masses of the Extremities: A Spectrum From Benign to Malignant. (15th March 2021) - Nijor, Sohn; Ali, Sayed; Ling, Stephen; Jonnalagadda, Padmaja
Abstract : Fat-containing masses are the most common solid, soft tissue masses encountered by radiologists and clinicians in everyday practice. The vast majority of these are benign. The imaging appearance of many fat-containing masses is frequently characteristic enough to suggest a specific diagnosis such as lipoma. However, there is a spectrum of benign and malignant fat-containing tumors with overlapping features. It is important to differentiate simple lipomas from well-differentiated liposarcomas due to differences in treatment, prognosis, and long-term follow-up. As molecular markers are increasingly being used for definitive characterization of tumors, we discuss their role and histopathologic characteristics of fat-containing soft tissue masses.